2015
DOI: 10.1293/tox.2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of changes in urinary and blood levels of biomarkers associated with proximal tubular injury in rat models

Abstract: To investigate useful biomarkers associated with proximal tubular injury, we assessed changes in levels of a focused set of biomarkers in urine and blood. Male rats administered a single dose or four doses of gentamicin (GM, 240 mg/kg/day) or a single dose of cisplatin (CDDP, 5 mg/kg) were euthanized on days 2 (the day after initial dosing) 5, or 12. At each time point, histopathological examination of the kidney and immunohistochemistry for biomarkers, kidney injury molecule-1 (Kim-1), lipocalin (NGAL), clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…By virtue of its small mass (MW ~12 kDa), β2-MG is filtered completely, as internalized by the proximal convoluted tubule through megalin-mediated endocytosis, and degraded [ 112 , 113 , 114 ]. Approximately 0.3% of filtered β2-MG is excreted in urine.…”
Section: Measurement Of Effects Of Cadmium On Kidneysmentioning
confidence: 99%
“…By virtue of its small mass (MW ~12 kDa), β2-MG is filtered completely, as internalized by the proximal convoluted tubule through megalin-mediated endocytosis, and degraded [ 112 , 113 , 114 ]. Approximately 0.3% of filtered β2-MG is excreted in urine.…”
Section: Measurement Of Effects Of Cadmium On Kidneysmentioning
confidence: 99%
“…Chronic KIM-1 expression can promote further tubulointestinal inflammation and hypoxia, further inducing KIM-1 expression that culminate in chronic kidney disease (Humphreys et al, 2013). The ectodomain of KIM-1 is shed into the lumen, and serves as a urinary biomarker of kidney injury (Bonventre, 2009, Kuwata et al, 2015, Jin et al, 2013). Recent study showed that KIM-1 may be released into the circulation and identified KIM-1 as a blood biomarker that specifically reflects injury to the proximal tubule of the kidney, the primary site of injury for ischemia and most nephrotoxicants (Sabbisetti et al, 2014, Bonventre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Blood elevation of KIM-1 is associated with lost polarity of tubule epithelial cells and increased trans-epithelial and microvascular permeability [26]. Experimental studies found significantly higher plasma KIM-1 (pKIM-1) levels in acute and chronic kidney injury [26,27]. In humans, the usefulness of blood (serum/plasma) KIM-1 was documented in AKI and CKD [21,26,28].…”
Section: Discussionmentioning
confidence: 99%